Thresholds for Epidemic Outbreaks in Finite Scale-Free Networks - Dong-Uk Hwang; S. Boccaletti; Y. Moreno; R. López-Ruiz (Mathematical Biosciences and Engineering)
We numerically investigate the existence of a threshold forepidemic outbreaks in a class of scale-free networks characterizedby a parametrical dependence of the scaling exponent, influencingthe convergence of fluctuations in the degree distribution. Infinite-size networks, finite thresholds for the spreading of anepidemic are always found. However, both the thresholds and thebehavior of the epidemic prevalence are quite different withrespect to the type of network considered and the system size. Wealso discuss agreements and differences with some analyticalclaims previously reported.